Clinical and laboratory profiles of hepatitis C in hemophiliac children - Hanifah Oswari; Ferry Damardjati S.P.; Djajadiman Gatot; Zakiudin Munasir; Julfina Bisanto (Paediatrica Indonesiana, 2007)
Background Hepatitis C virus (HCV) infection is common in hemophiliac receiving multiple coagulation factor transfusions before the introduction of donor screening and viral inactivation techniques. Information on the clinical profiles of HCV infection in children is still limited.Objective To describe clinical and laboratory profiles of HCV infection in hemophiliac children. Methods Patients registered at the Hemophilia Society of Department of Child Health, Cipto Mangunkusumo Hospital, who had positive anti-HCV were enrolled. None of them received antiviral treatment. All subjects infected by HCV before the age of 18 years and at least had positive anti-HCV test result for 6 months underwent clinical examination, alanine aminotransferase (ALT), platelets, and HCV RNA tests.Results Thirty nine subjects were available for review, with the median age of 15 years, and the mean age of the first time getting transfusion was 15 months. Twenty two (56%) of 39 subjects showed clinical manifestations. Liver and spleen enlargement were not found in any of the subjects. Ten (26%) subjects showed elevated ALT. Platelet count was within normal limit in all subjects. Twenty four (61%) patients had chronic hepatitis, whereas the remaining 15 (39%) subjects spontaneously cleared from HCV.Conclusions Pediatric HCV infection showed mild clinical manifestations. Sixty one percent subjects developed chronic hepatitis. The abnormality of laboratory finding may be associated with the future chronic liver disease.